The identity and revised circumscription of Centaurea iranshahrii (Asteraceae, Cardueae–Centaureinae) in Iran. Issue 3 (10th November 2015) - Negaresh, Kazem; Rahiminejad, Mohammad Reza
Abstract: New findings and a completed description are presented for Centaurea iranshahrii Wagenitz & Esfand (Asteraceae, Cardueae, Centaureinae). By adding new localities the distributional range of this species is circumscribed for the first time. Centaurea elymaitica Mozaff. is placed to synonymy of C. iranshahrii here. In addition, the only record of C. gudrunensis Boiss. & Hausskn. from Iran is rejected as referable to C. iranshahrii . Finally, the distribution and ecology of C. iranshahrii are presented and shown. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)